Foamed bitumen stabilised sandstone aggregates - Haji Abdul Karim, Roslinah (2015)
Roads form a key element for the expansion of economy and development of a country. As with most countries, Brunei Darussalam has been facing a rapid development to meet the economic growth that requires an efficient road network. Therefore, the scarcity of conventional road aggregates in Brunei Darussalam means that the country has a strong dependence on imported aggregates from overseas to construct quality roads. Further restrictions on local road specifications make it almost impossible to include low quality granular materials. The study reported in this thesis was undertaken on the basis that the dependence on overseas resources is not a viable long- term solution. The research task has been, therefore, to ascertain the quality of local sandstones for road construction and then to propose means to upgrade their performance quality for optimum utilisation in cost effective applications. This study focused on the road base layer since that is where most aggregate is used. The approach used for this study was to identify the common rock in Brunei Darussalam and review the candidate treatment methods. A weighted matrix for these candidate treatment methods was constructed to determine the overall ranking with selected key criteria on the basis of the local climatic condition, construction preferences and traditions. From the reviews, Foamed bitumen was selected as a feasible treatment method that can improve the sandstone characteristics under local conditions. Three curing conditions were adopted in this study, simulating extreme field conditions in Brunei Darussalam, to characterise the mechanical properties of foamed bitumen stabilised sandstone mixtures, termed 'foam mix'. The following tests were conducted: